Evaluation of Mastery of Pedagogic Competence of Physical Education, Sports and Health (PJOK) - Andhika Yudisthira; Damrah Damrah; Nurul Ihsan; Ronni Yenes; Jannatul Khairoh (UNIB Press, 2023)
This study aims to analyze and evaluate the mastery of PJOK teacher pedagogical competencies in the city of Padang. The research method used is qualitative research using the CIPP method. The sampling technique in this study was to use a total sampling technique involving 15 PJOK teachers at State Middle Schools in East Padang District. Data analysis techniques use qualitative research techniques with a data triangulation approach. The results of this study indicate that sports and health physical education teachers in terms of context have approached students so that it makes it easier for teachers to understand the characteristics of students. Evaluation of pedagogic competence in terms of the input that the teacher develops cognitive aspects as well as developing psychomotor aspects and affective aspects. a teacher must have a way to change the behavior of students in a better direction through an approach, providing motivation. Evaluation of teacher competence in terms of process, namely the teacher uses learning strategies depending on the situation and conditions then adapts to the media and demonstrates implementation, this is an obstacle due to the lack of teacher creativity in developing learning media so that the teacher only asks to model students who have talent in the field certain. The teacher also conducts midterm and final semester assessments and makes improvements in oral and written forms. In terms of product, many students have participated in championships at the city, provincial and even national levels. Students who take part in the championship even though they will be given extracurricular activities, they practice more outside, in other words, under the guidance of a club. Overall, the pedagodic competence of sports and health physical education teachers in Padang Timur District, Padang City, needs to be improved and improved in terms of context, input, process, and product.